Memahami pertobatan menurut St. Isaac the Syrian - Hia, Living Jovieli (Jurnal Teologi Cultivation, 2023)
By seeing that there are many Christians who ignore repentance, this article explains the concept of repentance from the point of view of St. Isaac The Syrian who said that repentance is not what we see, but tears that flow in a person through his encounter with God. In this study, the authors used the literature or library research method, which means studies that study various reference books and the results of previous research to answer the problem being studied. Therefore, repentance is a regret that brings a stream of tears and is maintained by being vigilant in prayer so that it reaches the perfection that needs to be offered to believers.